ANALISA MANFAAT INTERPROFESSIONAL EDUCATION PADA PENDIDIKAN DAN PRAKTIK KEPERAWATAN JIWA - Muhammad Agung Krisdianto, Maula Mar’atus Solikhah (AKPER Pemkab Purworejo, 2020)
Efforts to improve the quality of education are currently being made by starting to add learning methods that are more applicable and able to meet stakeholder demands. The World Health Organization (WHO) has launched a program to address human resource problems in health and the health service system by implementing collaborative practices among health workers. Interprofessional Education (IPE), also known as interprofessional learning, is an education concept recommended by WHO as integrated education to build collaboration between health workers. Objective: To analyze the benefits of IPE on mental health nursing education and practice. Methods: This study used a literature review method. PICO is used in selecting and determining article data to be used as material for a literature review. The data is processed using content analysis. Result: IPE is useful for mental health nursing education and practice based on scientific studies that have been conducted. Conclusion: IPE has benefits in nursing education and practice so that it can overcome problems that arise in mental health nursing.